Degradation of organic pollutants by Vacuum-Ultraviolet (VUV): Kinetic model and efficiency. (15th April 2018) - Xie, Pengchao; Yue, Siyang; Ding, Jiaqi; Wan, Ying; Li, Xuchun; Ma, Jun; Wang, Zongping
Abstract: Vacuum-Ultraviolet (VUV), an efficient and green method to produce hydroxyl radical (OH), is effective in degrading numerous organic contaminants in aqueous solution. Here, we proposed an effective and simple kinetic model to describe the degradation of organic pollutants in VUV system, by taking the OH scavenging effects of formed organic intermediates as co-existing organic matter in whole. Using benzoic acid (BA) as a OH probe, OH was regarded vital for pollutant degradation in VUV system, and the thus developed model successfully predicted its degradation kinetics under different conditions. Effects of typical influencing factors such as BA concentrations and UV intensity were investigated quantitatively by the model. Temperature was found to be an important influencing factor in the VUV system, and the quantum yield of OH showed a positive linear dependence on temperature. Impacts of humic acid (HA), alkalinity, chloride, and water matrices (realistic waters) on the oxidation efficiency were also examined. BA degradation was significantly inhibited by HA due to its scavenging of OH, but was influenced much less by the alkalinity and chloride; high oxidation efficiency was still obtained in the realistic water. The degradation kinetics of three other typical micropollutants including bisphenol A (BPA), nitrobenzene (NB) and dimethyl phthalate (DMP), and the mixture of co-existing BA, BPA and DMP were further studied, and the developed model predicted the experimental data well, especially in realistic water. It is expected that this study will provide an effective approach to predict the degradation of organic micropollutants by the promising VUV system, and broaden the application of VUV system in water treatment. Graphical abstract: Image 1 Highlights: A simple and effective kinetic model in VUV system was developed. Effects of typical factors were examined quantitatively. Quantum yield of .OH showed a positive linear dependence on temperature. The model predicted degradation kinetics of typical micropollutants well.